Color tunable up-conversion emission from ZrO2:Er3+, Yb3+ textile fibers. Issue 106 (1st November 2016) - Zhang, Xingshuang; Xu, Dong; Zhou, Guangjun; Wang, Xinqiang; Liu, Hongjing; Yu, Zhichao; Zhang, Guanghui; Zhu, Luyi
Abstract : ZrO2 : x Er 3+, y Yb 3+ fibers (diameters of approximately 1 μm) with good flexibility and toughness were synthesized via electrospinning technology, and color tunable up-conversion emissions were observed as the changes of Yb 3+ concentraion. Abstract : ZrO2 : x Er 3+, y Yb 3+ fibers (diameters of approximately 1 μm) with good flexibility and toughness were synthesized via electrospinning technology. The composition, morphology, and up-conversion photoluminescence properties of the fibers were investigated. The up-conversion photoluminescence mechanisms of ZrO2 fibers singly doped with Er 3+ ions or co-doped with Er 3+, Yb 3+ ions are also discussed in detail, including decay curves, and lifetimes. The main mechanisms in ZrO2 : x Er 3+, y Yb 3+ fibers were energy transfer from Yb 3+ to Er 3+ and cross relaxation processes between Yb 3+ and Er 3+ or between adjacent Er 3+ ions. When the concentration of Yb 3+ was 4 mol%, emission intensity over the entire spectrum and lifetime of the 2 H11/2 / 4 S3/2 → 4 I15/2 and 4 F9/2 → 4 I15/2 transitions in ZrO2 :Er 3+, Yb 3+ fibers were maximized using 980 nm excitation light. When the concentration of Yb 3+ was 20 mol%, pure red emission could be obtained. Different colors—green, yellow, and red—could be obtained with Er 3+ /Yb 3+ concentrations. Given the chemical, thermal, and mechanical stability of zirconia, Er 3+ /Yb 3+ co-doped ZrO2 up-conversion luminescence fibers may be an attractive choice for photonic materials.